Mathematics achievement based on gender among eight grade school students in Jordan - Rabab’h, Belal Sadiq Hamed; Veloo, Arsaythamby; Perumal, Selvan (2015)
The purpose of this study is to identify the differences in gender base on numbers, algebra, geometry and mathematics achievement among Jordanian 8th grade school students.The respondent of this study were 337 students from eight public secondary schools in Alkoura district and selected by using stratified random sampling. The study comprised of 179 (53%) males and 158 (47%) females students.The mathematics test comprises of 30 items which has eight items for numbers, 14 items for algebra and eight items for geometry.Finding from independent sample t-test shows that female student score higher than male students in numbers, algebra, mathematics achievement and spatial visualization.There is no significant difference in geometry base for gender.This study also indicates that numbers, algebra and mathematics achievement favorable to female and bias to male students.The main recommendations from this study are for teachers and other educational professionals to focus on the numbers and algebra for male students to improve the learning of mathematics, and feeding program through benefiting from tutorial classes to avoid of weakness in different aspects of mathematics achievement.Gender differences in mathematics in secondary school students in Jordan continue to exist and these differences may influence future educational and occupational pathways.